Two new glycosides isolated from Sapindus mukorossi fruits: effects on cell apoptosis and caspase-3 activation in human lung carcinoma cells. Issue 13 (2nd July 2016) - Zhang, Xuan-Ming; Yang, De-Po; Xie, Zhi-Yong; Li, Qing; Zhu, Long-Ping; Zhao, Zhi-Min
Abstract : Two new glycosides (1, 2 ) and two saponins (3, 4 ) were isolated from the fruits of Sapindus mukorossi Gaertn. The two glycosides were designated as sapindoside G (1 ) and 4′′, 4′′′′′- O -diacetylmukurozioside IIa (2 ). All four compounds exhibited inhibitory effects against A549 human lung adenocarcinoma cells with inhibition rates up to 69.2–83.3% at a concentration of 100 μg/mL. Flow cytometric analysis revealed that compounds1 –4 could suppress A549 cell growth by promoting cell apoptosis, which was related to the activation of caspase-3. Graphical abstract: